2013
DOI: 10.1007/s00464-013-3099-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for early gastric cancer with undifferentiated histology: could we extend the criteria beyond?

Abstract: ESD may be a feasible treatment for selected patients with undifferentiated EGC; this should be validated by development of new criteria for ESD for treatment of EGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…Among the 14 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] , we identified a total of 972 patients with EGC with undifferentiated-type histology. The clinical characteristics of the enrolled studies are shown in Tables 1-2 and Table 3.…”
Section: Characteristics Of Studies Included In the Final Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 14 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] , we identified a total of 972 patients with EGC with undifferentiated-type histology. The clinical characteristics of the enrolled studies are shown in Tables 1-2 and Table 3.…”
Section: Characteristics Of Studies Included In the Final Analysismentioning
confidence: 99%
“…All of the studies were conducted in Asia (10 studies in South Korea and 4 studies in Japan). Two studies were conducted in a multicenter setting [28,33] , whereas the remaining studies were conducted in a single center setting. Twelve English and 2 Korean studies were selected.…”
Section: Characteristics Of Studies Included In the Final Analysismentioning
confidence: 99%
See 3 more Smart Citations